(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2019)
أجريت الدراسة خلال الأعوام 2001 – 2003 على النوع azarolus التابع للجنس Crataegus L. حيث تمت دراسة كل من الورقة، عدد الأزهار ضمن العنقود الزهري، الإزهار ، الثمرة والبذرة للتمييز بين العينات التي أخذت من مجموعة أشجار موزعة على ستة مواقع في كل من محافظات: اللاذقية ، طرطوس، حماة. وبنتيجة تحليل التباين عند مستوى 5% لتحديد الاختلافات بين المعطيات الكمية للصفات بين العينات المدروسة تبين لنا وجود فروقات معنوية . وفيما يتعلق بالأوراق تفوقت أشجار موقع كسب في صفة طول الورقة وعرضها، أما من حيث مساحة نصل الورقة فقد تفوقت أشجار موقع برمانة المشايخ (طرطوس). فيما يتعلق بطول الثمار وعرضها ووزنها فقد تفوقت أشجار مواقع صلنفة ، الحفة ، مشيرفة الساموك على أشجار موقع عين سليمو (الغاب). كما بلغت أعلى نسبة للمواد الصلبة الذائبة في الثمار (17.67 %) في ثمار أشجار موقع كسب واقل نسبة في ثمار أشجار موقع صلنفة (11.67%). بينما كانت نسبة السكريات الأحادية في ثمار موقعي صلنفة وكسب (8.53%) متفوقة معنوياً على ثمار أشجار موقع عين سليمو (الغاب) التي كانت (5.04%). مما سبق يمكن القول أن أشجار النوع azarolus في المواقع المدروسة تمثل من حيث المبدأ ثلاث طرز وراثية وهذا ما سيتم إثباته لاحقاً من خلال البصمة الوراثية وبعض الصفات التصنيفية المعتمدة في البحث كدراسة حبوب الطلع. This study was carried out during 2001-2003 on Haw trees (Genus: Grataegus, Species: azarolus L.). Samples were collected from trees located in six sites in three provinces (Hafeh, Msherfet El-Samok, Kasab, Slunfeh sites in Lattakia Province; Premmanat El-Mashaikh site in Tartous Province, Ayn Salmo site in Al-Ghab – Hamah Province). Distinguishing between collected samples was conducted according to following aspects: Leaves, Number of flowers in the cluster, Flowering (Blossom), Fruits and Seeds. Significant differences between studied samples have been found when analysis study of variation at 5% level was done to determine the differences between quantitative data of studied aspects. Leaves of Haw trees collected from Kasab sits were the longest and widest, and the biggest leaf size of Haw trees has been found in samples collected from Premmanat El-Mashaikh site. Haw fruits collected from Slunfeh, Hafeh, and Msherfet El-samok sites, and from Ayn Salmo site were more significant in Length, Width, and Weight than the fruits from other sites. The highest percentage of soluble solid components of Haw fruits (17.67%) has been found in the fruits collected from Kasab site, whereas the lowest percentage (11.67%) was found in Haw fruits collected from Slunfeh site. The percentage of monosaccharide was more significant in Haw fruits collected from Slunfeh and Kasab sites (8.53%) compared to Haw fruits collected from Ayn Salmo site (5.04%). However we found that azarolus species in studied sites, consists of 3 types which need to be defined some tests other than the realized tests in our laboratory.